Novel mutation in coagulation factor VII (Carmel mutation): Identification and characterization. Issue 4 (25th February 2021) - Cassel, Aliza; Rosenberg, Nurit; Muhammad, Emad; Livnat, Tami; Dardik, Rima; Berl, Miriam; Preis, Meir
Abstract: Background: Measurement of factor VII (FVII) activity does not enable prediction of bleeding tendency in individuals with inherited FVII deficiency. Objective: To characterize the molecular and functional features of FVII in a family with FVII deficiency and correlate them with the bleeding tendency. Patients/Methods: We studied 7 family members with very low FVII activity using prothrombin time (PT), activated factor VII (FVIIa), FVII activity level, and thrombin generation. The factor 7 gene was sequenced and the mutation was analyzed by prediction software. Results: The proband has very low FVII activity (0%–4%), with PT ranging between 5% to 18% depending on the tissue factor (TF) origin. Direct sequencing demonstrated a single homozygous nucleotide substitution G > A in exon 6, predicting a novel missense mutation Cys164Tyr. Three members of the family were found to be heterozygous carriers of this mutation. One of them was a compound heterozygote, carrying both the Cys164Tyr and Ala244Val mutation (linked to Arg353Gln polymorphism). Her FVII activity and antigen levels were 3%–7% and 8%, respectively. The other heterozygous carriers demonstrated FVII activity of 41%–54%, FVII antigen of 46%–66%, and FVIIa activity of 30%. FVIIa was undetectable in the homozygous and compound heterozygous subjects. Thrombin generation was normal in the presence of calcium, but no response to TF addition was observed in the homozygous proband, and a reduced response was observed in the compound heterozygous subject. Conclusion: The patient homozygous for the "Carmel" mutation has mild clinical manifestations despite very low FVII activity, which correlates with thrombin generation results.